PERANCANGAN SISTEM DATA INVENTORY MENERAPKAN ALGORITMA SEQUENTIAL SEARCH PADA TOKO â€œALMELLSHOPZâ€ - Prasetiyo, Muhammad Hendrik; Lubis, Hendarman (JSI (Jurnal sistem Informasi) Universitas Suryadarma, 2024)
ALMELLSHOPZ is a shop that carries out buying and selling transactions for clothes, trousers and shoes. The problems that occur in the system that is currently running, namely for managing incoming and outgoing goods data, stock data, goods delivery data, customer data are still recorded in the ledger according to receipts containing how many goods came in and went out to be sent to customers. and stock inventory data is only recorded on a piece of paper and then copied back to the computer by the cashier, so that sometimes there are difficulti es in calculating goods and getting stock information is difficult, sometimes the information provided does not match the availability of existing goods. The aim of this research is to create a stock inventory data system, which can manage incoming and outgoing goods, stock of goods, goods delivery data, customer data using a Java-based sequential search algorithm method at the ALMELLSHOPZ store so that management data management activities are more efficient. One of the advantages of the Java programming language is that it is in great demand by developers and programmers because Java is a programming language that is multi-platform, aka universal and can be used on any platform. This makes many application developers use the Java programming language base to create the desired applications.Â